Pola Penderita Karsinoma Pankreas - Fienda Okta Via; Mizar Erianto; Mardheni Wulandari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Pancreatic carcinomas are the cells that develop into abnormal cells, which is why it is not that it is not controlled and develops in the pancreas. Pancreatic carcinoma is one of the deadliest cancers in the world, there are 330,000 deaths due to pancreatic carcinoma in 2012, and because of its very high mortality rate, pancreatic carcinoma is the leading cause of the seventh most common cancer death in the world, with a 5-year survival rate of 5%. This study aims to determine the pattern in patients with pancreatic carcinoma in the hospital Dr. H. Abdul Moeloek Bandar Lampung period January-December year 2019. The type of research used in this study is descriptive retrospective using a total sampling method and obtained a sample of 38 people. Patient data is obtained with secondary data of medical records. Based on the results of the study obtained the highest frequency distribution based on the age group of 51-60 years with a percentage of 36.8%, based on the gender of the male with a percentage of 76.3%, based on the procedure of operatives with a percentage of 68.4%, based on jaundice or non- jaundice, which is jaundice with the percentage of 71.1% And based on the predilection of the pancreas caput with a percentage of 71.1%. The conclusion is a pattern in patients with pancreatic carcinoma based on age, gender, procedure, jaundice, or non-jaundice and predilection.